Ownership structure, types of M&A and long-term performance - Mohd Hasimi Yaacob; Norazlan Alias (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study investigates the influence of ownership structure on long-term post-merger operating performance of acquirers. The findings reveal evidence of merger and acquisitions mitigating the long-term negative performance of acquirers. Board ownership variables have a positive and significant influence on the operating performance measures. Moreover, evidence supports the negative relationship at high substantial shareholder ownership levels. However, no evidence is found on the interaction effects between ownership structure variables and long-term post-merger performance of acquirer firms.